Pengaruh Kreativitas Mengajar Guru Terhadap Keaktifan Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas VIII SMP Negeri 1 Pangururan Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Mencelina Sihotang; Simion D. Harianja; Limmarten Simatupang; Lustani Samosir; Risden Anakampun (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this study was to determine the positive and significant effect of teacher teaching creativity on the activeness of learning Christian Religious Education and Budi Pekerti of class VIII students of SMP Negeri 1 Pangururan in the 2023/2024 academic year. The method used is quantitative inferential descriptive statistics. The population is all VIII grade students of SMP Negeri 1 Pangururan in the 2023/2024 academic year, totaling 191 people. The research sample was determined by random sampling (random) and a sample of 38 people was determined, namely 20% of the population. Data were collected with a positive closed questionnaire of 36 items. Thus it is known that there is a positive relationship between teacher's teaching creativity and students' activeness in learning Christian Religious Education and Budi Pekerti. 1) Correlation test obtained the value of rxy = 0.796> rtable (=0.05, n=38) = 0.320. 2) Effect test: a) Regression determination coefficient test (r2) = 63.4%. b) Regression equation test, obtained regression equation Y ̂ =